Data from: Functional traits, not productivity, predict openness to seedling recruitment in alpine plant communities under climatic warming - Meineri, Eric; Klanderud, Kari; Guittar, John; Goldberg, Deborah; Vandvik, Vigdis (Dryad, 2019)
Understanding the degree to which plant communities are open to seedling
recruitment is key to predicting how they will be impacted by climate
change. We experimentally assessed whether communities assembled under
colder climates were inherently more open to recruitment than
warmer-climate communities, after controlling for differences in the
current climate under which the communities were growing. We then tested
whether variation in openness to recruitment could be explained by
community biomass or by the plant functional traits of the community. The
study was conducted in a climate grid of twelve grassland sites across
southern Norway, differing systematically in temperature and
precipitation. Along a 2000 mm precipitation gradient, we transplanted
turfs with intact plant communities from alpine and sub-alpine sites into
2℃ warmer sites, and measured natural seedling emergence in these
transplanted turfs vs. locally replanted control turfs at the transplant
destination sites. Mixed effect models were used to assess the effect of
origin (cold vs warm climate), biomass, and functional trait composition
of the communities on seedling emergence. We further assessed variation in
these effects across different climatic contexts (the temperature and
precipitation gradients). Communities originating from colder climates
were consistently more open to recruitment, with on average 44% more
seedlings emerging, than the locally replanted control communities. The
higher rates of seedling emergence in colder-climate communities were
attributable to systematic differences in plant functional traits, but not
in biomass. The colder-climate communities were composed of species with
smaller leaves and lower maximum plant heights; traits that may make these
communities less effective at excluding new recruits. These trait-related
responses were not significant in the warmest sites and did not very
across the precipitation gradient. Our results suggest that alpine species
lack the competitive effect traits required to make their communities
resistant to invasion by novel competitors under climate change.
Dataset metadata and data dictionary for the data from the paper
“Functional traits, not productivity, predict openness to seedling
recruitment in alpine plant communities under climatic warming“ See README
file SEEDCLIM_TT_community opennes to
recruitmant.traits.biomass_2009.2011_data.xlsx
Keywords: emergence; Holocene; biotic interaction; invasibility; effect trait